Challenges and facilitators of professional socialization: A systematic review - Waliu Jawula Salisu; Nahid Dehghan Nayeri; Ibrahim Yakubu; Fatemeh Ebrahimpour (Wiley, 2019)
Abstract Aims This current study aimed to present a review of the challenges and facilitators of professional socialization among undergraduate nursing students. Design Systematic review. Methods A literature search was conducted in Embase, Google Scholar, PubMed and Scopus in April and May 2018 for studies published in the English language. Four thousand three hundred fifty‐two articles were retrieved. We conducted further screening for full‐text articles after discarding duplicates and irrelevant studies. Finally, eight studies were included. The Joanna Briggs appraisal tools were used to appraise and evaluate study quality. The PRISMA guidelines were followed and a narrative synthesis used for data analysis. Results Challenges and facilitators of professional socialization were identified and categorized into two major themes. Under each theme, results were grouped into three sub‐themes: professional, personal and educational challenges/facilitators.